Pengembangan Ornamental Landscape yang Berkelanjutan untuk Mengurangi Surface Urban Heat Island di Masjid Asy-Syifaa Kota Kendari - Nurgiantoro; Bahdad Bahdad; Jamal Harimuddin; Armayanti Aris; Muhammad Iqbal Kusumabaka Rianse; Fina Aulia; Muhammad Syafii; Reffi Anggriani; Riyan Fansuryah; Siti Nursakinah (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Revegetation based on the ornamental landscape is one of the efforts to reduce the surface of urban heat islands (SUHI), the intensity of which is always influenced by land surface temperature (LST). The focus of the PBM scheme community service program in the scope of PKM is disaster mitigation due to climate change, significantly reducing the risk of disasters due to LST. The program aims to reduce SUHI through vegetation modification using edible and ornamental plants as elements forming the landscape with a public education approach and revegetation actions. The results of PBM-PKM in public education activities show the high enthusiasm of the community in participating in activities and show that the level of partner understanding of the concept of revegetation has reached 100%. As a result of revegetation activities, as many as 342 edible plants and ornamental plant seeds invested in the community were successfully planted in the Asy-Syifaa Mosque, Kendari City landscape. The achievement of increasing the level of community empowerment shows a significant increase in understanding regarding the importance of creating vegetation in the yard landscape to reduce the risk of disasters due to rising LST through vegetation, which has been understood 100% by target partners. The results of monitoring and evaluating the growth of edible plants and ornamental plants as landscape-forming elements were able to grow well in the Asy-Syifaa Mosque area.